2013
DOI: 10.3856/vol41-issue5-fulltext-13
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in Pyropia columbina (Bangiales, Rhodophyta) under natural hydration and desiccation conditions

Abstract: ABSTRACT. In rocky shores, desiccation is triggered by daily tide changes, and experimental evidence suggests that local distribution of algal species across the intertidal rocky zone is related to their capacity to tolerate desiccation. In this context, the permanence of Pyropia columbina in the high intertidal rocky zone is explained by its exceptional physiological tolerance to desiccation. This study explored the metabolic pathways involved in tolerance to desiccation in the Chilean P. columbina, by charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 87 publications
4
21
0
Order By: Relevance
“…qPCR data were analyzed using C t values and the reference gene sen (Contreras‐Porcia et al. ; HE859069).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qPCR data were analyzed using C t values and the reference gene sen (Contreras‐Porcia et al. ; HE859069).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction. It was isolated from 1 g of fresh tissue according to Contreras-Porcia et al (2013). RNA yield and quality were assessed with the NanoDrop TM 1,000 Spectrophotometer (Thermo Fisher Scientific, Wilmington, DE, USA) and denaturing 1.2% formaldehyde agarose gel electrophoresis, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the life cycle, previous studies focused on characterization of the evolutionary aspects of the distinct stages [158,159], development of applied technologies including the designation of biomarkers [160], and treatments affecting the regulation of gene expression linked to reproductive processes [161]. A major focus for genomic research has been the interpretation and/or comparative analysis of transcriptomic data relating to the responses of laver species to abiotic stress [162,163], principally environmental conditions such as high temperature [164][165][166], repeated desiccation-rehydration [167,168], and hypersalinity [169].…”
Section: Future Issues: Identifying the Health-promoting Properties Omentioning
confidence: 99%
“…Transcriptome and microarray database of U. linza and C. crispus (Collen et al, 2007) has also evidenced the regulation of early light-induced proteins with higher expression under hyposaliny, high light and thermal stress; reduced expression in severe desiccation and unchanged under hypersalinity stress. In context to ROS attenuation by the antioxidant system during the hydration-desiccation cycle, several antioxidant enzymes and others including a peroxiredoxin, arachidonate 5-lipoxygenase, GSTs and several cytochrome P450 and HSPs (in hydrated thalli), whereas thioredoxin, CAT and low variants of HSPs70 and 90 (in desiccated thalli) were found upregulated in P. columbina analysed by suppression subtractive hybridisation and ESTs (Contreras-Porcia et al, 2013). Overexpression of many ribosomal protein genes and two ubiquitin ribosomal protein fusion genes in EST analysis of desiccation tolerant (Fucus vesiculosus) and susceptible (Fucus serratus) suggested that ribosome function and/or biogenesis are important during cycles of rapid desiccation and rehydration in the intertidal zone (Pearson et al, 2010).…”
Section: Functional Genomics -A Stepping Stone In Understanding the Smentioning
confidence: 99%
“…Overexpression of many ribosomal protein genes and two ubiquitin ribosomal protein fusion genes in EST analysis of desiccation tolerant (Fucus vesiculosus) and susceptible (Fucus serratus) suggested that ribosome function and/or biogenesis are important during cycles of rapid desiccation and rehydration in the intertidal zone (Pearson et al, 2010). Furthermore, accumulation of abscisic acid (ABA) in P. columbina during desiccation suggested its involvement in transcription of regulatory networks of desiccation stress signals and gene expression involving sugars, proline and PAs (Contreras-Porcia et al, 2013). In context to ROS attenuation by the antioxidant system during the hydration-desiccation cycle, several antioxidant enzymes and others including a peroxiredoxin, arachidonate 5-lipoxygenase, GSTs and several cytochrome P450 and HSPs (in hydrated thalli), whereas thioredoxin, CAT and low variants of HSPs70 and 90 (in desiccated thalli) were found upregulated in P. columbina analysed by suppression subtractive hybridisation and ESTs (Contreras-Porcia et al, 2013).…”
Section: Functional Genomics -A Stepping Stone In Understanding the Smentioning
confidence: 99%